Estudio de prefactibilidad para la instalación de una empresa de servicio de venta de comestibles vía e-commerce - Coronel Giles, Franz Enrique (2022)
The observed problem that gives rise to the research arises from the need to go to a physical store to purchase products of high rotation, taking into account all the appropriate sanitary measures, to acquire the products either weekly, monthly, among others. Faced with this problem, the project proposes a retail company that carries out the sale of large quantities and diversity of staple products through a virtual platform, from which you can select the desired products, place the order and the respective payment through online gateways. The market study estimated a demand for the project of 51 757 orders by 2026. Taking Metropolitan Lima's public households as a target, of NSE B and C; and a market share of 1,27%. As a result, the district of Pueblo Libre is chosen to be the ideal location for the company, due to a greater number of potential clients, proximity to suppliers, and lower land rental costs. Demand determines the size of the plant. The service capacity of the project is 142 orders per day. Finally, the total investment is determined at S/ 191 721, being 40% financed and 60% equity capital. After analyzing the economic cash flow, we obtain a Net Present Value of S/ 370 518 and an Internal Rate of Return of 93,25%; and from the financial analysis we obtain a Net Present Value of S/ 1 123 389 and an Internal Rate of Return of 144,46%. The project's profitability is proved because the Net Present Value is bigger than zero in both circumstances.